Complete Genome Sequence of the Persistent Listeria monocytogenes Strain R479a - Schmitz-Esser, Stephan (Genome Announc, 2015)
The complete genome sequence of the persistent Listeria monocytogenes strain R479a isolated from smoked salmon in Denmark and belonging to lineage II, serovar 1/2a, and multilocus sequence type 8 (ST8) is presented here.